SOME SEA SHELLS OF THE COASTAL REGION OF HUNEISH ISLAND SOUTHERN RED SEA , YEMEN - Khalaf, T. A .; Abubaker, M . M .; Abdul-Sahib, I. M.; Alshwafy, N . A. (Iraqi Journal of Aquaculture, 2022)
Sixteen species belonging to 9 families of gastropods and bivalves have been recorded from Huneish island, Yemen. Measurments, diagnosis and coloured photos for every specimen were provided .